The valorization of recreative program of walking by the side of participants: Middle aged women - Nešić Milan; Nešić Branimir; Perić Dušan (University Educons, Faculty of Sports and Tourism, Novi Sad, 2016)
Different programs of walking which are regularly practiced as content of recreation for a period of at least 60 minutes, thee happens in natural environment (foothpaths near river, woods, on the mountain, etc.) represent recommended physical activity which can have exceptionally positive influence on keeping and upgrading health. This transversal research was conducted within recreative program 'Walking up to Fruska Gora's monasteries', with the apply of Survay method. Goal was to make evaluation of some quality aspects of this program based on the perception of direct participants, with the establishment of metric characteristics of the scale PKPP. On the sample of 31 female sex examinee, aged from 35 to 57 years, questionnaire was applied for a conduct of the elements quality program. By analysis of the Scale Reliability Analysis, we got high Cronbach's Coefficient Alpha (,826). By Oblimin rotation of main components, we got stable monofactorial structure which shows that questionnaire can be applied as unique scale. Results of questionnaire found out that participants highly evaluated most of the quality aspects from chosen program of walking. There's none significant difference between scalar averages got in different subsamples which are formed compared to the years of life and habits for walking as regular recreative activity.